Influence of Green Marketing, Price, and Influencers on Millennials’ Eco-Friendly Purchases - PURNAMAWATI, Ida Ayu Putu Santi; DEWI, I Gusti Ayu Agung Istri Sari (Journal of Tourism Economics and Policy, 2025)
This study aims to comprehensively examine the influence of green marketing, price, and influencers on the purchasing decisions of eco-friendly products among millennials in Denpasar City. The research adopts a quantitative approach using a survey method, in which structured questionnaires were distributed to 100 respondents selected through simple random sampling. The collected data were analyzed through a series of validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that green marketing, price, and influencers each have a positive and significant effect on purchasing decisions, both simultaneously and partially. These findings highlight the crucial role of environmentally responsible marketing practices, competitive pricing strategies, and the persuasive impact of social media influencers in shaping millennial consumer behavior. Furthermore, the study offers practical implications for businesses seeking to strengthen sustainable marketing campaigns, as well as for policymakers aiming to encourage eco-friendly consumption patterns and support environmental sustainability initiatives in urban communities.